(untitled) (American Journal of Islam and Society, 2011)
Although—with a long way to go—the eighteen-day demonstrations in Egypt from January 25, 2011 to February 11, 2011, which toppled President Hosni Mubarak will ultimately go down in history as one of the great revolutions. This event stands alongside the French Revolution (1789–1799) and the Russian Revolutions (1917–1918). Almost everybody will agree that it was not a religiously motivated one, even though it was executed through an unprecedented cooperation between different religious groups and affiliations. In fact, this revolution was inspired by social, political, and economic concerns. However, with the majority of the Egyptians being Muslim (perhaps, because of that), and despite being un-Islamic itself, the Mubarak regime couldn’t resist both unleashing Islamic propaganda and appealing to Islamic sensibilities of the demonstrators in its effort to foil the demonstrations. Could or should these demonstrations have been thwarted by justifiable Islamic injunctions? This came through the Grand Mufti (the formal, highest Muslim authority) of Egypt, Dr. Ali Jum`ah, who made several pronouncements to discourage Muslim youth and their families from continuing to participate in the demonstrations. This brings forward some important questions: are peaceful demonstrations to remove a “despotic” leader and a “corrupt” government allowed (even if riddled with potential chaos)? Or should Muslims allow themselves to be ruled in perpetual tyranny and oppression in order to foster a lack of obvious chaos (not peace; as a tyrannical rule cannot be peaceful to the people themselves in the first place)? This editorial ...